Trask River Watershed Study: Fine benthic material sampling, 2008-2016 - Sherri L. Johnson (8106482) (2025)
These data are a portion of the larger Trask River Watershed Study which was conducted in the East Fork of the South Fork Trask River of the Coast Range of western Oregon. Basin-wide surveys of fine benthic particulates were conducted over the course of this study. In-stream deposition of fine sediments (< 1 millimeter) was quantified annually, during early summer. Samples were analyzed for standing stocks of the organic and inorganic fraction of surface and shallow subsurface materials. These surveys were conducted before and after land use treatments to provide insights into local and downstream effects. The Trask River Watershed study area consists of 4 large catchments: Pothole Creek, Gus Creek, Rock Creek, and Upper Main Trask. Within each of the four catchments, 2-4 headwater sites and a downstream site were sampled. In general, Trask River Watershed study data were collected during pre-harvest (2006-2011) and post-harvest (2013-2016) periods, from treated and reference headwater watersheds and from downstream sites. Sample reaches were 30 meters in length for headwater streams and 100 meters for downstream sites. Sampling for the fine benthic material began for all sites in June 2008, and continued annually in mid-June until 2016. Three replicates were taken from each headwater site and five from the downstream sites. For each replicate, a 15 centimeter diameter core was used to collect a surface sample and a subsurface sample (2-5 cm deep) from the streambed. The depth of the water within the core was measured to calculate the total volume present. For samples collected 2013-2016, a second depth measurement was recorded for the subsurface sample. After field collection, samples were taken to the lab and frozen. During processing, samples were thawed, filtered, dried, and ashed to calculate standing stocks of fine organic and inorganic material. These data are a portion of the larger Trask River Watershed Study. The general objectives of the Trask River Watershed Study were to investigate the effects of forest harvest on the physical, chemical and biological characteristics of small headwater streams, and the extent to which alterations in stream conditions caused by harvest along headwater channels influence the physical, chemical and biological characteristics of downstream fish-bearing streams. The primary role of this sampling was to characterize the abundance and composition of fine benthic particulate material. The organic fraction can be an important source of food for benthic detritivores, while the inorganic portion can have adverse affects on stream biota. Samples were collected from both surface and shallow subsurface (2-5 centimeters depth) habitats. For more information about these data and this study, see Johnson et al. (2022).